Low-Cost Fiber Optic Chemical Sensor Development for Fishpond Application - Budi Mulyanti; Yuski Maolid Rizki Faozan; Ajuni B. Pantjawati; Roer Eka Pawinanto; Lilik Hasanah; Wahyu Sasongko Putro (Universitas Ahmad Dahlan, 2018)
In this study, aimed to develop low-cost sensor based on fiber optic to assess ammonia index for fishpond application. Here, the simple design was proposed by using Evanescent wave type to assess ammonia index during acid rain event. The experiment result showed maximum absorption loss with variation ammonia mass 1 5% with wavelength 1310 nm from Optical Light Source (OLS) is 27.56 dBm while Optical Spectrum Analyzer (OSA) reached 25.86 dBm. We had calculated RMSE, MAE, and Percent Error (PE) value both of the device (Low-cost fiber optic chemical sensor and OSA) are 1.692%, 0.916%, and 98.833% respectively. A good result from low cost fiber optic chemical sensor has successful developed with lowest production less than 1,455 USD per-year.